Redoubling platinum group metal smelting intensity-operational challenges and solutions - Hundermark, R.; Nelson, L.; de Villiers, Bertus; Ndlovu, J.; Mokwena, D.; Mukumbe, P.; Pieterse, B.; Seyanund, W.; Van Manen, P. (2014)
The 2003 redoubling in power to 68MW on the Polokwane Smelter furnace represented a significant intensification in platinum group metal (PGM) smelting. Combined with onerous 'green' PGM concentrate smelting requirements, this yielded conditions unusually corrosive to copper coolers and refractories. This presented unexpected operational and design challenges to reliable crucible operation and maintenance. Combined with specific operational control intervention, development of protective coatings has led to the life of water-cooled copper components improving from 9 to 40 months. The furnace matte endwall was extended in 2010 to address accelerated wear of refractories and the potential risk for contact of copper components by superheated matte. An 18 month planned endwall rebuild cycle has been demonstrated (versus catastrophic failure within 9 months). Finally, benefits including lower energy consumption, improved metal recoveries and higher productivity resulting from operational and in-house design developments will be described, that justify "Celebrating the Mega-scale" in PGM smelting.